Penerapan Process Selection dan System Design pada Industri Pembuatan Parfum Natural Berbasis Bahan Alami - Safira, Olivia; Zulkhairatullail; Lusiana (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The natural perfume industry has experienced rapid growth due to increasing consumer awareness of environmentally friendly and sustainable products. This trend requires manufacturers to select appropriate production processes and design operational systems capable of accommodating diverse natural ingredients, flexible formulation development, and consistent product quality. This study aims to analyze the application of process selection and system design in the development of a natural perfume production industry from an operations management perspective. A conceptual study approach was employed using the process–volume matrix and facility layout analysis as analytical frameworks. The results indicate that a combination of batch and job shop processes is the most suitable production method for small to medium-scale natural perfume industries, as it provides greater flexibility in product variation and formulation development. Furthermore, the implementation of a process layout combined with a cellular system can improve workflow efficiency while maintaining consistent product quality. These findings highlight that flexible and adaptive operational system design plays a crucial role in supporting the sustainable development of the natural perfume industry.